2015
DOI: 10.1177/0004563215589382
|View full text |Cite
|
Sign up to set email alerts
|

Age-adjusted glycated albumin accurately reflects blood glucose in patients with neonatal diabetes mellitus: comparison with calculated glycated albumin determined by past blood glucose concentrations

Abstract: Background: Glycated albumin is a useful glycaemic control indicator for neonatal diabetes mellitus. However, glycated albumin concentrations in infants are lower than those in adults and increase in an age-dependent manner. Based on our investigation of non-diabetic subjects, we proposed the possibility that the reference range for adults may be used regardless of age, provided that age-adjusted glycated albumin is employed. In the present study, we evaluate the usefulness of age-adjusted glycated albumin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Recently, we found that Aa-GA is a more accurate blood glucose indicator in patients with NDM based on the fact that mean blood glucose has strong positive correlation with Aa-GA (16). In this study, we obtained the new findings that Aa-GA at diagnosis in the patients with NDM is potentially affected by the age of diagnosis.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Recently, we found that Aa-GA is a more accurate blood glucose indicator in patients with NDM based on the fact that mean blood glucose has strong positive correlation with Aa-GA (16). In this study, we obtained the new findings that Aa-GA at diagnosis in the patients with NDM is potentially affected by the age of diagnosis.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, we reported that age-adjusted GA (Aa-GA) is applicable to all ages with the reference value for adults and that it is possible to evaluate glycemic control by using Aa-GA (15). Indeed, we showed that Aa-GA accurately reflects blood glucose in patients with NDM by comparing it with calculated glycated albumin determined by past blood glucose concentrations (16).…”
Section: Introductionmentioning
confidence: 99%
“…The normal control HbA1c and GA levels are in the range of 4.6%‐6.2% and 11.0%‐16.0%, respectively. Age‐adjusted GA was calculated using the following formula that has been described in a previous report: Age adjusted 0.25em normalG normalA 0.25em = 0.25em normalG normalA 0.25em × 0.25em 14.0 0.25em false/ 0.25em [] 1.77 0.25em × 0.25em normallog () age , 0.25em normalin 0.25em days 0.25em prefix+ 0.25em 6.65 . …”
Section: Methodsmentioning
confidence: 99%
“…In an analysis of non‐diabetic subjects, there was a strong correlation between GA and log‐transformed age, from newborns to adults . We confirmed that age‐adjusted GA would accurately reflect glycemic control status in NDM …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation